Pseudospin-electron model in the self-consistent gaussian fluctuation approximation - Stasyuk, I.V.; Tabunshchyk, K.V. (Condensed Matter Physics, 2001)
Pseudospin-electron model with an effective many-body interaction between pseudospins via conducting electrons is investigated within the generalized random phase approximation scheme with the self-consistent inclusion of mean field type contributions (coming from the effective pseudospin interaction) as well as gaussian fluctuations of the mean field (which makes it possible to obtain more accurate results in the vicinity of the critical points). Using the approach proposed here, the expressions are obtained for the pseudospin correlation function, for pseudospin mean value, as well as for the grand canonical potential. В роботі пропонується аналітична самоузгоджена схема розрахунку термодинамічних і кореляційних функцій у псевдоспін-електронній моделі при відсутності кореляцій. Отримано аналітичні вирази для псевдоспінової кореляційної функції, середнього значення оператора псевдоспіну та термодинамічний потенціал в узагальненому наближенні хаотичних фаз при врахуванні поправок типу середнього поля, що виникають внаслідок ефективної взаємодії псевдоспінів через електрони провідності, а також при врахуванні гаусових флуктуацій середнього поля.